How successful people think change your thinking, change your life - Maxwell, John C. 1947- (Hachette Audio, 2009)
Shares the eleven secrets that successful people use to succeed in life and work, including seeing beyond one's own needs, removing mental distractions, working with others, and examining the past for a better understanding of the future